2008
DOI: 10.1200/jco.2007.11.8513
|View full text |Cite
|
Sign up to set email alerts
|

Phase I-II Study of Oxaliplatin, Fludarabine, Cytarabine, and Rituximab Combination Therapy in Patients With Richter's Syndrome or Fludarabine-Refractory Chronic Lymphocytic Leukemia

Abstract: The OFAR regimen is highly active in RS and has activity in fludarabine-refractory patients with CLL. This regimen warrants further investigation in the treatment of these disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 143 publications
(113 citation statements)
references
References 36 publications
(6 reference statements)
4
109
0
Order By: Relevance
“…This principle has been clinically validated, as relapse-free survival is extended with combinations of cyclophosphamide and fludarabine (Eichhorst et al, 2006;Catovsky et al, 2007;Flinn et al, 2007). New combinations of nucleoside analogs and platinum derivatives with complementary mechanisms of action and non-overlapping side effect profiles may further increase activity (Tsimberidou et al, 2008). These studies validate strategies that target DNA repair mechanisms and suggest that this may be an important step in the development of novel approaches for overcoming drug resistance to DNAtargeting chemotherapeutics.…”
Section: Targeting Dna Repair In Quiescent Cellsmentioning
confidence: 90%
“…This principle has been clinically validated, as relapse-free survival is extended with combinations of cyclophosphamide and fludarabine (Eichhorst et al, 2006;Catovsky et al, 2007;Flinn et al, 2007). New combinations of nucleoside analogs and platinum derivatives with complementary mechanisms of action and non-overlapping side effect profiles may further increase activity (Tsimberidou et al, 2008). These studies validate strategies that target DNA repair mechanisms and suggest that this may be an important step in the development of novel approaches for overcoming drug resistance to DNAtargeting chemotherapeutics.…”
Section: Targeting Dna Repair In Quiescent Cellsmentioning
confidence: 90%
“…Rituximab has been successfully applied in the clinic in combination with Fludarabine, or Fludarabine and Dexamethasone, and Mitoxantrone. 1,2 We sought to investigate the mechanisms of Rituximab-induced apoptosis in chronic lymphocytic leukemia cells through the upregulation of AU-rich binding proteins that can target certain mRNAs for degradation. 3,4 We found that 20 mg/ml of Rituximab induced apoptosis when crosslinked with an anti-human Fcg-specific antibody (referred to as XRituximab), especially at 48 h post-stimulation as measured by either propidium iodide alone or Annexin V-propidium iodide methods, which is in agreement with earlier work.…”
mentioning
confidence: 99%
“…Rapidly enlarging lymph nodes, increasing LDH level, new onset of B symptoms (fever, night sweats, and weight loss greater than 10%), and poor response to usual CLL therapies support the diagnosis of RT (6). Unfortunately, the clinical features of RT are non-specific, and suggestive laboratory findings can also frequently be seen in patients without RT.…”
Section: Discussionmentioning
confidence: 99%